Northwest history. Mining. Discovery. 1927-02-17 (1927)
Richmond hits large ore body. Ten-foot holes in side of drift fail to find limit, says official. High grade milling ore in a body of large but undetermined size has been struck in the Carlisle mine of the Richmond Yukon Copper, near Whitehorse, Y.T. The announcement is made by John B. White, president, Spokane, in a circular letter mailed to the stockholders yesterday.